People socialize ecological information about the environment but may forget their own experiences: a case study of local ecological knowledge about seed-dispersing animals - Santos, Gilney Charll; Sousa Júnior , José Ribamar de; Nascimento, André Luiz Borba do; Silva, Josivan Soares da; Feitosa , Ivanilda Soares; Schiel, Nicola; Araújo, Elcida de Lima; Nóbrega Alves, Rômulo Romeu; Albuquerque, Ulysses (Ethnobiology and Conservation, 2024)
Local ecological knowledge (LEK) has been increasingly used in the search for efficient strategies to maintain biological diversity. However, considering the rapid environmental changes in ecosystems, such knowledge may have been lost between generations, affecting its potential application. In this study, we adopted the LEK of the potential dispersers of Caryocar coriaceum Wittm. (Caryocaraceae), an endangered plant species of socioeconomic and cultural importance from northeast Brazil, as a model. We evaluated whether there is intergenerational variation in the LEK about the abundance of Dasyprocta prymnolopha (the principal disperser of C. coriaceum) associated with the local practice of hunting. We collected LEK data from 39 hunter-gatherers aged 31 to 84 years, and camera traps were used during two annual C. coriaceum harvests to record its potential dispersers. Our results indicate that the LEK of the potential animal dispersers of C. coriaceum does not vary between generations; it is disseminated and shared between different generations. The strong interactions among people during the C. coriaceum harvest period facilitate the sharing of information about the potential dispersers of this species. Our results show that hunting D. prymnolopha does not depend on perceptions regarding the availability of this resource in the forest, which may be causing overexploitation. Therefore, local knowledge may need to be updated and connected to the recent and rapid environmental changes because people may believe that current environmental conditions are like those of the past. If this is the case, people may be less cooperative with conservation strategies because they are not aware of environmental changes, so measures to update knowledge about environmental conditions may be necessary to encourage effective participation in management and conservation plans.